2019
DOI: 10.1038/s41598-019-52088-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural phenolic compounds potentiate hypoglycemia via inhibition of Dipeptidyl peptidase IV

Abstract: Dipeptidyl peptidase IV (DPP IV) is a surface glycoprotein that can degrade glucagon like pepetide-1 (GLP-1) by decreasing blood sugar. Herbal medicines for diabetic therapy are widely used with acceptable efficacy but unsatisfied in advances. DPP IV was chosen as a template to employ molecular docking via Discovery Studio to search for natural phenolic compounds whether they have the inhibitory function of DPP IV. Then, docking candidates were validated and further performed signal pathway via Caco-2, C2C12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
(42 reference statements)
2
25
0
1
Order By: Relevance
“…Curcumin is the major constituent of turmeric ( C. longa ), that various reported activities including anti-tumour, anti-malaria, immunomodulation, and anti-diabetes effects [ 26 ]. In fact, the anti-diabetic effects of curcumin are exerted by activating the peroxisome proliferator-activated receptors γ (PPAR γ) signalling pathway and upregulating GLUT4 translocation [ 12 ], increasing insulin secretion and sensitivity, regulating glucagon synthase kinase 3 (GSK-3) [ 27 ], and inhibiting DPP-4 activity [ 28 ]. Previously, curcumin and its derivatives (curcuminoids) had been proved as α-glucosidase inhibitors in an enzymatic manner [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is the major constituent of turmeric ( C. longa ), that various reported activities including anti-tumour, anti-malaria, immunomodulation, and anti-diabetes effects [ 26 ]. In fact, the anti-diabetic effects of curcumin are exerted by activating the peroxisome proliferator-activated receptors γ (PPAR γ) signalling pathway and upregulating GLUT4 translocation [ 12 ], increasing insulin secretion and sensitivity, regulating glucagon synthase kinase 3 (GSK-3) [ 27 ], and inhibiting DPP-4 activity [ 28 ]. Previously, curcumin and its derivatives (curcuminoids) had been proved as α-glucosidase inhibitors in an enzymatic manner [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, HCD and berberine interacted with Tyr 662 and Tyr 666 around the binding site and showed stronger inhibitory activities than those of rutin and quercetin. This impact could also be evaluated from the binding simulation of curcumin in a previous study [14]. This result speculated that interaction with Tyr 662 and Tyr 666 might be more important than others.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous study, rutin, quercetin, and berberine showed DPP-4 inhibitory potency while docking with DPP-4 [14]. In the literature, the hypoglycemic effect of berberine has been investigated for many years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations